Peptides rapidly transport antibiotic across the intact tympanic membrane to treat a middle ear infection - Arwa Kurabi; Emily Sereno; Allen F. Ryan (Drug Delivery)
The tympanic membrane (TM) forms an impenetrable barrier to medical therapies for middle ear (ME) diseases like otitis media. By screening a phage-displayed peptide library, we have previously discovered rare peptides that mediate the active transport of cargo across the intact membrane of animals and humans. Since the M13 filamentous bacteriophage on which the peptides are expressed are large (nearly 1 µm in length), this offers the possibility of noninvasively delivering drugs, large drug packages, or gene therapy to the ME. To evaluate this possibility, EDC chemistry was employed to covalently attach amoxicillin, or neomycin molecules to phage bearing a trans-TM peptide, as a model for large drug packages. Eight hours after application of antibiotic-phage to the TM of infected rats, ME bacterial titers were substantially reduced compared to untreated animals. As a control, antibiotic was linked to wild-type phage, not bearing any peptide, and application to the TM did not affect ME bacteria. The results support the ability of rare peptides to actively deliver pharmacologically relevant amounts of drugs through the intact TM and into the ME. Moreover, since bacteriophage engineered to express peptides are viral vectors, the trans-TM peptides could also transport other viral vectors into the ME.